Pengaruh Bank Sampah Terhadap Perilaku Pengelolaan Sampah Rumah Tangga dan Kepedulian Lingkungan di Desa Baturagung Kecamatan Gubug Kabupaten Grobogan Tahun 2019 - Ahmad, Syakir; Samidjo, Jacobus (Indonesian Journal of Geography Education; Vol 1 No 1 (2020): Indonesian Journal of Geography Education, 2020)
The garbage bank is one of the solutions to overcome the problem of household waste management and can increase public awareness of the environment in the village of Batur agung, Gubug District. The purpose of this study is to manage household waste through the waste bank and find out whether there is a influence of the waste bank on the behavior of household waste management and to know whether there is a influence of the waste bank on the environmental care of the community in the village of Batur agung, Gubug sub-district. While the method used by the author here is the method of data collection which includes: observation methods, interview methods, documentation methods and questionnaire or questionnaire methods. The analytical method used in this research is descriptive analysis and to find the correlation coefficient between X and Y variables is using Product Moment correlation analysis . Then to find out the influence of waste banks on the behavior of household waste management and environmental awareness using simple linear regression analysis with the help of the SPSS program. From the results of the study show that firstly, garbage banks have a significant and positive effect on the behavior of household waste management with an impact level of 70%, secondly, a waste bank has a significant and positive effect on environmental awareness with an impact level of 80%.